Answer:
(x, y) = (3, 26)
Explanation:
I like to solve systems of equations like this by graphing. A graphing calculator easily shows the solution for both x and y.
(x, y) = (3, 26)
__
As an alternative, here, the equations can be subtracted.
y = f(x)
y = g(x)
0 = f(x) - g(x) . . . . subtract the second equation from the first
0 = 11x -7 -(3x +17)
0 = 8x -24 . . . . simplify
0 = x -3 . . . . . . .divide by 8
3 = x
Now, we can substitute into either equation:
y = g(x) = 3(3) +17 = 26
The solution is (x, y) = (3, 26).